Zoonoses parasitárias veiculadas por alimentos de origem animal: revisão sobre a situação no Brasil - Rossi, Gabriel Augusto Marques; Hoppe, Estevam Guilherme Lux; Martins, Ana Maria Centola Vidal; Prata, Luiz Francisco (Instituto Biológico, 2014)
Brazil is one of the most important countries in the production of animal source foods, and the consumers are looking for safe and innocuous products for health. In this context, it is necessary to prevent zoonosis that can be transmitted by animal source foods, which are sometimes consumed without proper cooking or made by vulnerable populations. On this review, important parasitic zoonotic diseases will be covered, which currently occur by this transmission route: toxoplasmosis, taeniasis-cysticercosis complex, cryptosporidiosis, anisakiasis, diphyllobothriasis and trichinosis.

O Brasil se destaca na produção mundial de alimentos de origem animal, sendo que cada vez mais os mercados consumidores buscam alimentos seguros e inócuos para a saúde. Nesse contexto, torna-se fundamental a prevenção das zoonoses, que podem ser transmitidas através dos alimentos de origem animal, que muitas vezes são consumidos sem o devido preparo ou por populações mais vulneráveis. Nesta revisão bibliográfica, serão abordadas importantes enfermidades parasitárias de caráter zoonótico que ocorrem atualmente pela via de transmissão alimentar: a toxoplasmose, o complexo teníase-cisticercose, criptosporidiose, anisacose, difilobotriose e triquinelose.
Foodborne parasitic zoonosis: a review of the situation in Brazil
Keywords: zoonoses; enfermidades parasitárias; alimentos de origem animal; zoonosis; foodborne parasitic diseases; foods of animal origin